Prevalence of Metallo β-Lactamase Genes Among MDR Pseudomonas Aeruginosa Isolated from Different Sources in Baghdad - Saidmurad, Mustafa Azm; Al-Jubori, Sawsan Sajid; Edbeib, Mohamed Faraj (Al-Mustansiriyah Journal of Science, 2024)
Background: Pseudomonas aeruginosa is a gram-negative apportunistic pathogen that has ability to couse different type of infections and charecterised by their high resistance to commonly used antibiotics via different stratiges. Objective: The objective of this study is to detect the prevalence rate of MβL gene among MDR Pseudomonas aeruginosa. Methods: Forty clinical isolates of Pseudomonas aeruginosa were obtained from different hospitials in Baghdad/Iraq. Their identification was confirmed by using 16s rDNA as a housekeeping gene (reference gene). Specific primers were used to detect 3 types of Metallo β-lactamase (MβL) genes vim, spm1, and imp1 genes followed by sequencing the amplified fragment which was analyzed by Geneious software. Antibiotic sensitivity test for 15 antimicrobial agents was done using the Kirby-Bauer disc diffusion method. Results: The revealed resistance pattern was as following: 100% for the combination of Trimethoprim/Sulphamethoxazole and Nitrofurantoin, 95% for Tigecycline, 82.5% for Ciprofloxacin, 67.5% for Cefepime, 60% for Levofloxacin, 57.5% for Carbenicillin, 55% for Piperacillin, 50% for Amikacin, 47.5% for Tobramycin, 45% for both Imipenem and Ceftazidime, 27.5% for piperacillin/tazobactam, 22.5% for Aztreonam and 7.5% for Colistin. More than half (55%) of isolates were positive for MβL enzymes production during phenotypically assessed by combined disc test. The MIC of meropenem ranged from 16µg/ml to 32 µg/ml. The percentage of MβL genes among the total isolates during conventional PCR was as follows: 95% for vim, 25% of the isolates harbored both vim and imp1, while spm 1 are negative in all isolates. The result of the study explained that 10 isolates from the antibiotic susceptibility test were resistant to 10-14 antimicrobial agents that harbored both vim and imp1 genes. Conclusions: MβL gene could be used as a genetic marker to determine the degree of resistance in MDR P. aeruginosa which are more resistant than other isolates that have one gene of MβL responsible for break the β-lactam ring then inactivating the β-lactam antibiotic.